STEM-Engineering Design Process (EDP) Learning to Increase Students' Learning Motivation on Solar System Topic - Shofiah Jihni; Nanang Winarno; Achmad Samsudin; Rika Magdalena Aritonang (Indonesian Journal of Science and Education, 2024)
Learning in the fields of science, technology, engineering, and mathematics, or STEM, is the focus of attention not only by school teachers but also all stakeholders involved. Various efforts have been made to improve the quality of the learning process and curriculum in these fields. The activities students do during learning are influenced by motivation, so motivation is very important for students to complete tasks and build knowledge. This study aims to analyze the improvement of students' learning motivation by using the STEM-Engineering Design Process (EDP) on the topic of the Solar System. This study used a pre-experimental method with One Group Pretest-Posttest. The data collection tool used in this study is the Motivation Sefl regulation questionnaire. This research was conducted in one of the schools in Bandung, Indonesia. The subjects in this study were 25 seventh-grade students consisting of 11 boys and 14 girls. The results showed a significant increase in students' learning motivation with a mean pretest of 76% and a mean posttest of 89%. Based on the average N-Gain score of 0, 51, the four dimensions are interpreted as obtaining a moderate N-Gain. Based on the study's results, it was found that STEM-Engineering Design Process (EDP) learning can increase students' learning motivation, especially in science lessons.